2020
DOI: 10.3390/cancers13010107
|View full text |Cite
|
Sign up to set email alerts
|

Potentially Modifiable Factors Associated with Adherence to Adjuvant Endocrine Therapy among Breast Cancer Survivors: A Systematic Review

Abstract: Adjuvant endocrine therapy (AET) reduces risk of breast cancer recurrence. However, suboptimal adherence and persistence to AET remain important clinical issues. Understanding factors associated with adherence may help inform efforts to improve use of AET as prescribed. The present systematic review examined potentially modifiable factors associated with adherence to AET in accordance with PRISMA guidelines (PROSPERO registration ID: CRD42019124200). All studies were included, whether factors were significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
71
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(79 citation statements)
references
References 108 publications
1
71
0
Order By: Relevance
“…Greater self-efficacy was associated with higher self-reported adherence at baseline. This is consistent with ample literature linking self-efficacy and adherence among AET users 15 and others with chronic illness (eg, HIV/AIDS; cardiovascular, and respiratory disorders). 50 Bandura’s social cognitive theory outlines how personal factors (including cognitions such as self-efficacy), behaviour, and environmental factors all reciprocally influence each other to affect behaviour change.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Greater self-efficacy was associated with higher self-reported adherence at baseline. This is consistent with ample literature linking self-efficacy and adherence among AET users 15 and others with chronic illness (eg, HIV/AIDS; cardiovascular, and respiratory disorders). 50 Bandura’s social cognitive theory outlines how personal factors (including cognitions such as self-efficacy), behaviour, and environmental factors all reciprocally influence each other to affect behaviour change.…”
Section: Discussionsupporting
confidence: 87%
“…It is unsurprising that side effects are relevant to adherence, as they are reportedly responsible for AET discontinuation in half of those who discontinue. 46 However, a recent systematic review reported that measures of side effects are associated with adherence or persistence in approximately half of studies that measure them, 15 suggesting that side effects alone might not reliably predict adherence. Side effects being common among AET users, 47 , 48 factors beyond side effect presence or severity, such as reaction to side effects, or having effective management strategies (such as those outlined by Franzoi et al) 49 may be relevant to understanding adherence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pain and insomnia also contribute to the progression of fatigue and mental distress that further worsen symptom burden, leading to poor quality of life [8][9][10] . In breast cancer patients, pain and psychological symptoms like insomnia and depression are associated with early discontinuation and non-adherence to adjuvant hormonal therapy and, consequently, poor clinical prognosis [11][12][13][14] . In recent decades, timely and proper management of insomnia and pain has been identified as a critical element of comprehensive cancer care and several validated therapies have emerged as effective insomnia treatments 15,16 .…”
Section: Introductionmentioning
confidence: 99%
“…Endocrine therapy for breast cancer mainly reduces or clears estrogen levels in the body through some drugs or treatments, thereby inhibiting the growth of breast cancer and reducing the risk of recurrence and metastasis [5,6], which plays an important role in the comprehensive treatment of breast cancer [7]. Studies [8][9][10][11][12] show that most patients with endocrine therapy for breast cancer have experienced hot ashes, night sweats, insomnia, joint stiffness, weight gain, anxiety, depression and other symptoms, and the long treatment cycle will make patients become depressed and indifferent. Therefore, in the process of treatment and rehabilitation of patients with breast cancer endocrine therapy, it is particularly important for patients to actively participate in the management of the disease and establish an effective self-management model.…”
Section: Introductionmentioning
confidence: 99%